The Relation Between Upper Respiratory Tract Infection (URTI) and Allergic Rhinitis with Acute Otitis Media in THT-KL Polyclinic RSUDZA Banda Aceh - Azzahra, Irchi Amanda; Kurnia, Benny; Alia, Dina; Husnah; Nurjannah (AVERROUS: Jurnal Kedokteran dan Kesehatan Malikussaleh, 2025)
Acute otitis media (AOM) is an inflammation of part or all of the middle ear mucosa, including the eustachian tube, mastoid antrum, and mastoid cells, occurring within less than three weeks, accompanied by local symptoms such as fever, pain, reduced hearing, and discharge. Several diseases that are risk factors for AOM include a history of upper respiratory tract infections (URTI) and allergic rhinitis. This study aims to determine the relationship between URTI and allergic rhinitis with AOM at the ENT-KL Polyclinic of RSUDZA Banda Aceh from January 2022 to December 2023. This observational analytical research employs a cross-sectional design. The study utilized medical record data with total sampling techniques, resulting in a sample size of 2.178 people. Data analysis was performed using the Chi-square test. The results indicated that 227 people (10,4%) experienced AOM, 448 people (20,6%) had URTI and 225 people (10,3%) had allergic rhinitis. The age characteristics of patients with the most ear disorders was 55-64 years, namely 409 people (18.8%), and the dominant gender was female, namely 1175 people (32.9%). The Chi-square test results for URTI and AOM showed a p-value of 0.033 (PR=1.35, 95% CI 1.02-1.79), indicating that there is a relationship between URTI and AOM. Similarly, the Chi-results for allergic rhinitis with AOM yielded a p-value of <0.001 (PR=2.26, 95% CI 1.69-3.02), suggesting a relationship between allergic rhinitis and AOM. It can be concluded that patients with URTI are approximately 1,35 times more likely to suffer from AOM, while patients with allergic rhinitis are about 2,26 times more likely to develop AOM.